Fluorophore Release from a Polymethinic Photoremovable Protecting Group Through a Nonlinear Optical Process. Issue 9 (3rd July 2017) - Rodríguez‐Romero, Jesús; Guarin, Cesar A.; Arroyo‐Pieck, Andres; Gutiérrez‐Arzaluz, Luis; López‐Arteaga, Rafael; Cortés‐Guzmán, Fernando; Navarro, Pedro; Peon, Jorge
Abstract: Triggering the release of chemical species through the use of light is crucial for modern microscopy applications, such as single‐molecule localization and, in general, in the regulation of molecular effectors. Herein, we demonstrate a nonlinear‐optical scheme for the control of photorelease. Our system consists of a two‐photon‐absorbing photoremovable protecting group (PPG) bonded to a second chromophore which undergoes photo‐induced detachment and activation upon excitation with λ =850 nm femtosecond pulses. The two‐photon PPG section consists of a cyanine‐type dye, and the releasable section is a highly fluorescent derivatized anthracene chromophore bonded to the cyanine through a photolabile etheric‐ meso ‐carbon bond. This method allows for the release of a fluorophore following a spatially localized two‐photon excitation event. Both the excitation energy and the long lifetime of the upper excited states of the PPG chromophore are thought to be involved in the release process. Abstract : Let it go, let it go ! A new molecular design for the photocontrolled release and activation of a fluorophore is presented. The system consists of a two‐photon‐absorbing photolabile protecting group fragment (a cyanine‐type dye) bonded to a second chromophoric moiety (a fluorescent anthracene derivative) which undergoes photoinduced release upon biphotonic excitation with 850 nm femtosecond laser pulses.